Brazil-Russia: similarities, parallels, differences. Paradoxes of the phenomenon of transition 68 - L. S. Okuneva (Ибероамериканские тетради, 2015)
In the article are considered criteria and possibilities of comparative analysis of the processes of political modernization of Brazil and Russia that unfolded there at the turn of the 1980s-1990s. The article deals with the features of the formation of civil society and political culture on the stage of a radical transformation of political structures in both countries (party system, the role of political leadership, etc.). Also the article investigates character of the differences in the development of the both countries at the beginning of the XXI century.